GABAergic motor neurons bias locomotor decision-making in C. elegans - Ping Liu (Nature Portfolio, 2020)
Motor neurons are generally considered to be passive receivers of commands from other neurons. However, this study shows that motor neurons may shape locomotor behaviour by regulating premotor neurons, and that premotor neurons serve to integrate information from sensory neurons and motor neurons.